THE IMPACT OF NATURE ON THE LIFESTYLE OF DALAT PEOPLE - Trần Thị Hiền (Tạp chí Khoa học Đại học Đà Lạt)
Based on the fieldwork data and some relevant studies, the article analyzes the impact of nature on forming the lifestyle of Dalat people. The study shows that some specific natural ecological environment factors of Lang Biang Highland including the climate, terrain, and landscape have played a role in shaping the "gentle, elegant, and hospitable" feature in cultural patterns, conducts, and behaviors of Dalat people. Therefore, in discussions on how to preserve and promote the lifestyle of Dalat people, it should be brought into consideration the conservation and restoration of the landscapes and the ecological environment of this plateau town.